2022
DOI: 10.1007/s10926-022-10026-x
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Mental Illness Disclosure Outcomes in the Work Context: A Cross-Sectional Study Among Dutch Workers

Abstract: Purpose The decision whether to disclose mental illness at work can have important positive and negative consequences for sustainable employment and well-being. The aim of the study is (1) to examine workers’ expectations of outcomes of mental illness disclosure in the workplace and to evaluate their expectations regarding which factors are of influence on these outcomes, (2) to identify distinct subgroups of workers, and (3) to characterize these subgroups in terms of personal, sociodemographic, and work-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
6
0
3
Order By: Relevance
“…These stigma-related concerns were significantly associated both with non-disclosure intentions and decisions. Stigma has been found to be a barrier to disclosure before, both in military, other trauma-prone occupations and civilian populations 5 6 16 33 34. When comparing the results of the current study to a study among Dutch civilian workers, it should be noted that of military personnel who had not disclosed, half reported seeing themselves as weak and being ashamed, compared with only 13.5% of civilians 18.…”
Section: Discussionmentioning
confidence: 50%
“…These stigma-related concerns were significantly associated both with non-disclosure intentions and decisions. Stigma has been found to be a barrier to disclosure before, both in military, other trauma-prone occupations and civilian populations 5 6 16 33 34. When comparing the results of the current study to a study among Dutch civilian workers, it should be noted that of military personnel who had not disclosed, half reported seeing themselves as weak and being ashamed, compared with only 13.5% of civilians 18.…”
Section: Discussionmentioning
confidence: 50%
“…This review highlights the urgent need to understand the long-term effects of stigma on employment and implement destigmatization interventions in the workplace. Van Beukering et al [48] explored Dutch workers' anticipated outcomes of disclosing mental illnesses in the workplace through a cross-sectional survey and found that, while most workers held an optimistic view of disclosure, they also anticipated potential discrimination, emphasizing the complexity and dual nature of mental health disclosure among workers to support sustainable employment. In supporting employees with chronic illnesses, Bosma [49], along with other researchers, explored the views of occupational physicians and organizational representatives on supporting employees with chronic diseases.…”
Section: Research On the Impact Of Workplace Interventions And Psycho...mentioning
confidence: 99%
“…Also, a recent study showed that 64% of Dutch line managers were reluctant to hire a job applicant with a mental health issue ( 6 ). In addition, 68.4% of Dutch workers expected that disclosure during a temporary contract would decrease the chance that a contract would be renewed, and 56.6% expected that disclosure would lead to a diminished chance to be promoted to a higher position in the future ( 7 ). MHI affect a large part of the population, almost half of the adults (48%) in Netherlands (18–75 years old) has ever had one or more mental illnesses ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Netherlands, several studies have shown that a variety of workplace stakeholders tend to have negative attitudes towards people with MHI, such as HR managers, line managers and coworkers ( 1 , 6 , 7 , 19 , 20 ). However, research on this topic is very scarce in Netherlands, especially on attitudes of workers in non-managerial positions, who often make up a large part of the social work environment.…”
Section: Introductionmentioning
confidence: 99%